SIRT1 and SIRT2 Activity Control in Neurodegenerative Diseases - Manjula, Ramu; Anuja, Kumari; Alcain, Francisco J. (Frontiers in Pharmacology, 2021)
Sirtuins are NAD+ dependent histone deacetylases (HDAC) that play a pivotal role in neuroprotection and cellular senescence. SIRT1-7 are different homologs from sirtuins. They play a prominent role in many aspects of physiology and regulate crucial proteins. Modulation of sirtuins can thus be utilized as a therapeutic target for metabolic disorders. Neurological diseases have distinct clinical manifestations but are mainly age-associated and due to loss of protein homeostasis. Sirtuins mediate several life extension pathways and brain functions that may allow therapeutic intervention for age-related diseases. There is compelling evidence to support the fact that SIRT1 and SIRT2 are shuttled between the nucleus and cytoplasm and perform context-dependent functions in neurodegenerative diseases including Alzheimer’s disease (AD), Parkinson’s disease (PD), and Huntington’s disease (HD). In this review, we highlight the regulation of SIRT1 and SIRT2 in various neurological diseases. This study explores the various modulators that regulate the activity of SIRT1 and SIRT2, which may further assist in the treatment of neurodegenerative disease. Moreover, we analyze the structure and function of various small molecules that have potential significance in modulating sirtuins, as well as the technologies that advance the targeted therapy of neurodegenerative disease.